Review of emerging contaminants in aquatic biota from Latin America: 2002–2016. (28th October 2016) - Llorca, Marta; Farré, Marinella; Eljarrat, Ethel; Díaz‐Cruz, Sílvia; Rodríguez‐Mozaz, Sara; Wunderlin, Daniel; Barcelo, Damià
Abstract: Although it is known that emerging contaminants are widespread all over the globe, there is a gap of information about their distribution in some geographical areas, such as Latin America. The present bibliographic work reviews the available literature about the presence of organic emerging contaminants in Latin American freshwater and marine biota between 2002 and 2016 and includes 23 works from Argentina, Brazil, Chile, Colombia, Mexico, and Nicaragua. In particular, the present review provides an overview of the occurrence of continuously present contaminants such as pharmaceuticals, personal care products, and pyrethroid insecticides, as well as the new groups of persistent organic pollutants, the halogenated flame retardants and the perfluoroalkyl substances. A wide overview is provided, considering not only occurrence data but also effects and potential transfer through the food chain. Environ Toxicol Chem 2017;36:1716–1727. © 2016 SETAC